P121 Identification and active management of secondary adrenal insufficiency in SLE reduces risk of relapse. (23rd March 2020) - Rhodes, Benjamin; Ahmad, Haroon; Logan, Sarah; Rankin, Elizabeth; Hewins, Peter
Abstract : Background: Steroids are an important component of Lupus treatment, but long-term use is associated with an accumulation of damage, emphasising the importance of optimising steroid withdrawal protocols. The factors influencing successful steroid withdrawal in SLE are poorly understood. Secondary adrenal insufficiency is common following therapeutic steroid usage, but the prevalence in steroid-treated lupus patients is undocumented. We documented rates of adrenal insufficiency and evaluated whether actively managing steroid withdrawal influenced the risk of disease relapse. Methods: 137 SLE patients who had been on Prednisolone for more than a year before reducing the dose below 5 mg/day for the first time were retrospectively reviewed, documenting the clinician decision to screening for adrenal insufficiency, the frequency of adrenal insufficiency, the method of steroid reduction (stopping vs. tapering regimens), clinical, pharmacological and immunological variables. Parameters influencing the risk of relapse from the point of dropping below 5 mg/day of Prednisolone were evaluated by Cox' regression. Results: 65 patients were screened for adrenal insufficiency. 38% failed initial screening and 12% showed no signs of adrenal recovery after more than a year. 46.7% returned to higher dose steroids, with 34% having a true disease relapse (BILAG A or B flare). In a multivariate model the decision to screen for adrenal insufficiency was the variable most strongly associated with risk of disease relapse (BILAG A/B flare) (marginal Hazard Ratio 4.33, P=0.0001), followed by complement C4 at baseline and South Asian ancestry. Concomitant medications or the method of steroid reduction (stopping vs. tapering) did not influence relapse. A full analysis of factors associated with failed adrenal screening and risk of disease relapse will be presented. Conclusions: Adrenal insufficiency in common in patients with SLE and unless screening takes place this may go undetected. Detection and active management of adrenal insufficiency is associated with a significant and meaningful reduction in disease relapse.